Research analysis on the physical preservation of Daluang and European paper manuscripts in the Scopus database - Salim, Tamara Adriani; Azmir, Aviazka Firdhaussi; Sani, Mad Khir Johari Abdullah (Universitas Padjadjaran, 2025)
Background: The preservation of cultural heritage manuscripts has long been guided by conservation techniques developed for European paper. However, Daluang paper behaves differently from Western paper, raising concerns about the suitability of directly applying European methods to its care. Purpose: This study aimed to compare the physical preservation between Daluang manuscripts and European paper manuscripts, for which different methods were used to preserve cultural heritage. Methods: A total of 38 peer-reviewed articles were analyzed using a systematic literature review (SLR) from the Scopus database between 2015 – 2025. Results: The findings provided evidence on the susceptibility of Daluang manuscripts to fungi and moisture-induced degradation, particularly in tropical countries. In European paper manuscripts, changes in acidity often lead to corrosion. Protection methods for Daluang manuscripts focus on environmental adjustments of and preventative measures, whereas European paper requires chemical treatments, such as acid reduction or phytate-based ink protection. Conclusions: This study concludes that multilateralism is needed for manuscript preservation, with underpinning principles grounded in conservation science, cultural heritage, and the analytical investigation of materials. More localized research and conservation are urgently needed for endangered collections such as the Daluang manuscripts. Implications: These findings imply that conservation implementation must be adapted to the material characteristics, historical trajectories, and environmental contexts of each manuscript, as demonstrated by European and Daluang traditions. In practice, this implies the urgency of developing localized, preventive conservation strategies integrated with digitization to support sustainable preservation and broader access.